Long-term effect of low frequency stimulation of STN on dysphagia, freezing of gait and other motor symptoms in PD. Issue 9 (13th April 2018) - Xie, Tao; Bloom, Lisa; Padmanaban, Mahesh; Bertacchi, Breanna; Kang, Wenjun; MacCracken, Ellen; Dachman, Abraham; Vigil, Julie; Satzer, David; Zadikoff, Cindy; Markopoulou, Katerina; Warnke, Peter; et al.
Abstract : Objective: To evaluate the long-term effect of 60 Hz stimulation of the subthalamic nucleus (STN) on dysphagia, freezing of gait (FOG) and other motor symptoms in patients with Parkinson's disease (PD) who have FOG at the usual 130 Hz stimulation. Methods: This is a prospective, sequence randomised, crossover, double-blind study. PD patients with medication refractory FOG at 130 Hz stimulation of the STN were randomised to the sequences of 130 Hz, 60 Hz or deep brain stimulation off to assess swallowing function (videofluoroscopic evaluation and swallowing questionnaire), FOG severity (stand–walk–sit test and FOG questionnaire) and motor function (Unified PD Rating Scale, Part III motor examination (UPDRS-III)) at initial visit (V1) and follow-up visit (V2, after being on 60 Hz stimulation for an average of 14.5 months), in their usual medications on state. The frequency of aspiration events, perceived swallowing difficulty and FOG severity at 60 Hz compared with 130 Hz stimulation at V2, and their corresponding changes at V2 compared with V1 at 60 Hz were set as primary outcomes, with similar comparisons in UPDRS-III and its subscores as secondary outcomes. Results: All 11 enrolled participants completed V1 and 10 completed V2. We found the benefits of 60 Hz stimulation compared with 130 Hz in reducing aspiration frequency, perceived swallowing difficulty, FOG severity, bradykinesia and overall axial and motor symptoms at V1 and persistent benefits on all of them except dysphagia at V2, with overall decreasing efficacy when comparing V2 to V1. Conclusions: The 60 Hz stimulation, when compared with 130 Hz, has long-term benefits on reducing FOG, bradykinesia and overall axial and motor symptoms except dysphagia, although the overall benefits decrease with long-term use. Clinical trial registration: NCT02549859 ; Pre-results.